Relationship Between Fulfillment Of Pre-Operative Fluid Needs And The Incidence Of Nausea And Vomiting In Patients Post General Anesthesia At Dr Saiful Anwar Hospital, East Java Province - Wahyu Triono; Reny Tri Febriani; Puguh Raharjo (PROFESSIONAL HEALTH JOURNAL, 2025)
A head injury is scary. Head injuries can be fatal and require medical attention. Trauma severity evaluation helps clinicians make informed judgements, create effective treatment plans, reduce time and costs, and maybe prevent brain injury impairment and death. A comprehensive physiological grading system, the Revised Trauma Score evaluates human physiological function. This study examines the relationship between the Revised Trauma Score and head injury fatalities at RSUD dr. Saiful Anwar Malang. The research uses cross-sectional and observational correlation analytic methods. The study sampled 70 people incidentally. Used secondary data from observation sheets and medical records. The majority of 46 respondents (65.7%) had RTS scores of 11-12, indicating low brain injury. Despite the high mortality rate, 57 respondents (81.43%) survived. Spearman rank test two variables for correlation. The study found a 0.000 p-value between the RTS category and head injury mortality at RSUD Dr. Saiful Anwar Malang. Lighter RTS categories have lower mortality rates, while heavier ones have higher rates. RTS's effectiveness in predicting head injury death needs further study.